The role of Public Entrepreneurship Orientation orientation and organizational learning capability on organizational performance mediated by innovation in service (study on top management of government institutions) - Yulianti, Ida; Prabandari, Sri Palupi; Barinta, Dunga Dwi; Kurniasari, Irma (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
Organizational Performance is a very important aspect for the success of an organization. Good organizational performance is not only necessary for business enterprises, but it is also essential in running public service organizations such as government institutions. An organization with good performance will be able to produce quality products or services, increase customer satisfaction, and achieve the organization's strategic goals. Therefore, organizational performance in government institutions is very important to ensure the effectiveness and efficiency of quality governance. This study aims to identify the factors that drive the improvement of organizational performance in the public sector. This research will analyze the role of intrapreneurship and organizational learning capabilities in driving the improvement of organizational performance in the public sector. Additionally, this study aims to analyze and explain the mediating effect of service innovation on the relationship between organizational learning capabilities and organizational performance. This research is innovative in measuring organizational performance in public sector organizations. Generally, research on organizational performance measurement is conducted in business enterprises. This study is expected to reveal the factors that shape organizational performance in public sector organizations, so that public sector organizations can be more creative, innovative, transparent, and responsive in providing public services. This study employs a quantitative research method using surveys or questionnaires, which involve collecting information by compiling a list of questions to be asked of respondents. The findings of this study fully support the findings of previous research. This study found that entrepreneurial interest is one of the factors that can optimize the role of the family environment and entrepreneurship education in strengthening the self-efficacy of prospective young entrepreneurs in Indonesia.